Molecular cloning, functional assessment and transcriptome characterization of cysteine protease inhibitor and kunitz trypsin inhibitor from turmeric (Curcuma longa L.) - Chan, Seow Neng (2016)
Protease inhibitors (PIs) are biochemical compounds commonly found in all organisms; function to regulate proteases activities in cell. Plant PIs such as cysteine protease inhibitor (CYP) and Kunitz trypsin inhibitor (KTI) have been reported to show anti-pathogenic properties and are responsible for the plant tolerance against various stresses. Similar to other plant defence-related proteins, numerous plant PIs genes have been characterized and expressed as recombinant proteins for industrial applications or genetically inserted into crop plants for phytoprotection. However, the effectiveness of these applied plant defence-related proteins (including PIs) in combating the targeted pathogens slowly weakens as there are continuous adaptation processes and resistance developed by pathogens. One important approach to overcome this is to discover and incorporate the use of new PI genes from novel sources where they have not been exposed to the pathogens before. The objectives of this study are to characterize novel PI genes from turmeric, Curcuma longa, as turmeric extracts were reported to contain numerous medicinal properties including inhibition of viral proteases. The identified PI genes were to be expressed as recombinant proteins and their functional activities were assessed. Besides, this study also aimed to generate a transcriptomic library of Curcuma longa for future molecular biology works. Initially, complementary-DNA (cDNA) fragments of CYP and KTI were identified from leaf samples of Curcuma longa treated with methyl jasmonate by using degenerate polymerase chain reaction (PCR). The full-length cDNAs, designated CypCl and ClKTI, were obtained by using rapid amplification of cDNA ends method (RACE) with complete open reading frames (ORFs) detected. The cDNA sequences have been deposited in NCBI database with the accession number KF545954.1 (CypCl) and KF889322.1 (ClKTI). The expression profile of CypCl and ClKTI genes in methyl jasmonate treated tissues was determined by using Real-Time quantitative-PCR (RT-qPCR) and it was found that the PIs genes were generally induced in all treated tissues. Both PIs were cloned into expression vectors and recombinant protein expressions were optimised in the bacterial-host systems. Optimum incubation temperature and concentrations of isopropyl β-D-1-thiogalactopyranoside (IPTG) used for the recombinant protein expression was determined at 37ºC and 0.5 mM of IPTG for 2 hours induction. The recombinant CypCl was expressed as soluble protein while recombinant ClKTI was expressed as inclusion bodies. Recombinant CypCl was purified using immobilized metal affinity chromatography (IMAC) and anion-exchange chromatography while recombinant ClKTI was solubilized and refolded before purification by IMAC. The concentration of the purified recombinant CypCl obtained was 5 μg/μL and the refolded ClKTI was 1 μg/μL. The purified recombinant proteins were shown to possessed protease inhibitory activities but did not show obvious anti-pathogenic potential from screenings performed using agar plate well-diffusion method. Lastly, transcriptomic library of Curcuma longa was generated through next-generation sequencing (NGS), RNA-seq, from RNA of differently treated leaf samples using Illumina Hiseq platform. The de novo transcriptome assembly was conducted from the combined raw RNA-seq reads by using Trinity software and resulted in 113,209 assembled transcripts. Around 50% of the assembled transcripts were found to be functional annotated which included gene ontology (GO) terms annotation by the sequence homology search performed on known proteins from different databases by using Trinotate software. The differential expressed genes (DEG) in the methyl jasmonate-treated sample as compared to the control were identified with 1,559 upregulated transcripts and 2,715 downregulated transcripts. In conclusion, two novel PI genes (CYP and KTI) were identified from turmeric and their expressions profiling were characterized. Recombinant expression in E. coli system, refolding and purification of PIs were optimised and inhibitory activities were suggested from the inhibitory assays while weak to resistance anti-pathogenic potential were concluded from the tested fungi. Finally, a transcriptome library of turmeric was obtained and the transcripts were annotated and analysed.